Harmonization of Legal Policies Regulating Minimum Standards for Transportation of People on Electric Rail Trains - Churniawan, Erifendi; R R Siti Kuswati, Atir; Nopriyanto, Windi (International Journal Labs, 2024)
There is disharmony in the Minister of Transportation Regulation on Minimum Train Services, which is disharmonious, as are the provisions in the Railway Traffic Regulation and the Railway Law. This can occur because each formulator of the Railway Law, Railway Traffic Regulation, and Minister of Transportation Regulation on Minimum Train Services is a different institution. This has the potential to cause disharmony in the legislation and affect its implementation, which is not optimal. This research discusses efforts to formulate legal harmonization so that the regulations in the Minister of Transportation of Minimum Train Services, the Railway Law, and the Railway Traffic Regulation can be in line and facilitate their implementation. This research is normative legal research. As a normative legal research, the main focus is on the analysis aspect of laws and regulations. The approaches used in this research are statutory approach and conceptual approach. The research results are legal disharmonization in the policy of setting the minimum standard of transportation of people on KRL disharmonization occurs vertically. The main factor that causes legal disharmony is the existence of sectoral ego in each agency. Therefore, the sectoral ego in each agency can be overcome by structured and coordinated coordination to ensure excellent and interrelated rules. The effort is to carry out vertical harmonization by involving various related agencies. This is to ensure that one rule and another rule have the same spirit and orientation so as not to cause problems in practice.